Study the corrosion behaviour of aluminium alloy 5052 in Croton Megalocarplus and Coconut Biodiesel / Premdass Deva Ray - Premdass, Deva Ray (2018)
Biodiesel has become more attractive as alternative fuel for engines because of its environmental benefits and the fact that it is made from renewable sources. However, corrosion of metals in biodiesel is one of the concerns related to biodiesel compatibility issues. This study aims to characterize the corrosion behaviour of aluminium alloy 5052 commonly encountered in the fuel system in diesel engine. The biodiesel was tested in this study is croton megalocarpus biodiesel and coconut biodiesel. Static immersion tests in B0, B10, B20 and B30 fuels were carried out at room temperature for 1200 h for both of the biodiesel. At the end of the test, corrosion behaviour was investigated by weight loss measurements and changes in surface morphology. The surface morphology was analysed using SEM images. Viscosity of the fuel was also analysed using Anton paar viscometer to co-relate the viscosity of the blends towards the corrosion. Results showed that under the experimental conditions, aluminium alloy 5052 is more corrosion resistant in presence of coconut biodiesel and its blends compare to croton megalocarpus biodiesel and its blends. All the objective as per listed earlier of the study was clearly achieved for this study.